2008
DOI: 10.3117/rootres.17.91
|View full text |Cite
|
Sign up to set email alerts
|

A Leaf wilting in sugar beet (Beta vulgaris L.) based on varietal difference of root system.

Abstract: Thirteen varieties/strains of sugar beet were cultivated in haplic andosol and the relationship between root system distribution and resistance to high temperature and dry soil conditions was investigated during the hot summer of 2006. We found that there were clear differences on the degree of leaf wilting among thirteen varieties/strains. When leaves of other varieties had wilted despite closing stomata to reduce water loss, the leaves of 'Kabutomaru' did not wilt. Based on the degree of leaf wilting, 'Kabut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In our ratoon harvesting system, the regrowth period coincided usually with the dry season, which was further worsened by unusually small precipitation in 2016, resulting in dry soil. Sugar beet, which belongs to the same family as spinach, with shallower root systems (due to soil type or beet cultivar) wilts more promptly in summer dry season (Hayashi et al 2004, Itoh et al 2008. Therefore, roots in the subsoil would facilitate a smooth growth of the plants in dry conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our ratoon harvesting system, the regrowth period coincided usually with the dry season, which was further worsened by unusually small precipitation in 2016, resulting in dry soil. Sugar beet, which belongs to the same family as spinach, with shallower root systems (due to soil type or beet cultivar) wilts more promptly in summer dry season (Hayashi et al 2004, Itoh et al 2008. Therefore, roots in the subsoil would facilitate a smooth growth of the plants in dry conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of varietal differences in root expansion habit to plant growth has also been observed in different crops. Itoh et al (2008) reported that varietal differences in the root system distribution of sugar beets affected the responses of the plants to heat and dryness. More extensive and detailed studies are necessary to confirm the contribution of hop genotypes to cone yield as a result of root expansion habit.…”
Section: Discussionmentioning
confidence: 99%